Makassar City and Public Space Without Siri' and Pacce - Ahmadin (Jurnal Ilmu Sosial dan Humaniora, 2023)
Siri' and Pacce are a philosophy of life as well as a value system that guides the lives of the Bugis and Makassar people and other ethnic groups in South Sulawesi. The importance of this value is that the essence of existence and the meaning of human life according to the people in this area is largely determined by the practice of the Siri' value, as in the classic expression Siri' is what differentiates humans from animals. As time progresses and social changes occur, there is a degradation of the value of Siri' and it tends to no longer be part of society's social system. This paper examines the phenomenon of social life in Makassar City, especially in public spaces which have ignored the Siri' and Pacce values, forms of value degradation, as well as the importance of revitalizing these noble local cultural values. This is important as the saying that the condition of a city is a reflection of the people who live there.